Implication of Apatite and Anhydrite for Formation of an Iron‐Oxide‐Apatite (IOA) Rare Earth Element Prospect, Benjamin River, Canada. Issue 4 (4th September 2017) - Hoshino, Mihoko; Watanabe, Yasushi; Kon, Yoshiaki
Abstract: The Benjamin River apatite prospect in northern New Brunswick, Canada, is hosted by the Late Silurian Dickie Brook plutonic complex, which is made up of intrusive units represented by monzogranite, diorite and gabbro. The IOA ores, composed mainly of apatite, augite, and magnetite at Benjamin River form pegmatitic pods and lenses in the host igneous rocks, the largest of which is 100 m long and 10–20 m wide in the diorite and gabbro units. In this study, 28 IOA ore and rock samples were collected from the diorite and gabbro units. Mineralogical observations show that the apatite–augite–magnetite ores are variable in the amounts of apatite, augite, and magnetite and are associated with minor amounts of epidote‐group minerals (allanite, REE‐rich epidote and epidte) and trace amounts of albite, titanite, ilmenite, titanomagnetite, pyrite, chlorite, calcite, and quartz. Apatite and augite grains contain small anhydrite inclusions. This suggests that the magma that crystallized apatite and augite had high oxygen fugacity. In back scattered electron (BSE) images, apatite grains in the ores have two zones of different appearance: (i) primary REE‐rich zone; and (ii) porous REE‐poor zone. The porous REE‐poor zones mainly appear in rims and/or inside of the apatite grains, in addition to the presence of apatite grains which totally consist of a porous REE‐poor apatite. This porous REE‐poor apatite is characterized by low REE (<0.84 wt%), Si (<0.28 wt%), and Cl (<0.17 wt%) contents. Epidote‐group minerals mainly occur in grain boundary between the porous REE‐poor apatite and augite. These indicate that REE leached from primary REE‐rich apatite crystallized as allanite and REE‐rich epidote. Magnetite in the ores often occurs as veinlets that cut apatite grains or as anhedral grains that replace a part of augite. These textures suggest that magnetite crystallized in the late stage. Pyrite veins occur in the ores, including a large amount of quartz and calcite veins. Pyrite veins mainly occur with quartz veins in augite. These textures indicate pyrite veins are the latest phase. Apatite–augite–magnetite ore, gabbro–quartz diorite and feldspar dike collected from the Benjamin River prospect contain dirty pure albite (Ab98 Or2 –Ab100 ) under the microscope. The feldspar dikes mainly consist of dirty pure albite. Occurrences of the dirty pure albite suggest remarkable albitization (sodic alteration) of original plagioclase (An25.3 –An60 in Pilote et al., 2012) associating with intrusion of monzogranite into gabbro and diorite. SO4 2− bearing magma crystallized primary REE‐rich apatite, augite and anhydrite reacted with Fe in the sodic fluids, which result in oxidation of Fe 2+ and release of S 2− into the sodic fluids. REE, Ca and Fe from primary REE‐rich apatite, augite and plagioclase altered by the sodic fluids were released into the fluids. Then Fe 3+ in the sodic fluids precipitated as Fe oxides and epidote‐group minerals in apatite–augite–magnetite ores. Finally, residual S 2− in sodic fluids crystallized as latest pyrite veins. In conclusion, mineralization in Benjamin River IOA prospect are divided into four stages: (1) oxidized magmatic stage that crystallized apatite, augite and anhydrite; (2) sodic metasomatic stage accompanying alteration of magmatic minerals; (3) oxidized fluid stage (magnetite–epidote group minerals mineralization); and (4) reduced fluid stage (pyrite mineralization). Abstract : REE leaching from apatite and decomposition of anhydrite by sodic fluids are important for formation and REE mineralization of Benjamin River IOA prospect.